Local and landscape drivers of predation services in urban gardens. Issue 3 (21st March 2017) - Philpott, Stacy M.; Bichier, Peter
Abstract: In agroecosystems, local and landscape features, as well as natural enemy abundance and richness, are significant predictors of predation services that may result in biological control of pests. Despite the increasing importance of urban gardening for provisioning of food to urban populations, most urban gardeners suffer from high pest problems, and have little knowledge about how to manage their plots to increase biological control services. We examined the influence of local, garden scale (i.e., herbaceous and arboreal vegetation abundance and diversity, ground cover) and landscape (i.e., landscape diversity and surrounding land use types) characteristics on predation services provided by naturally occurring predators in 19 urban gardens in the California central coast. We introduced sentinel pests (moth eggs and larvae and pea aphids) onto greenhouse‐raised plants taken to gardens and assigned to open or bagged (predator exclosure) treatments. We found high predation rates with between 40% and 90% of prey items removed in open treatments. Predation services varied with local and landscape factors, but significant predictors differed by prey species. Predation of eggs and aphids increased with vegetation complexity in gardens, but larvae predation declined with vegetation complexity. Smaller gardens experienced higher predation services, likely due to increases in predator abundance in smaller gardens. Several ground cover features influenced predation services. In contrast to patterns in rural agricultural landscapes, predation on aphids declined with increases in landscape diversity. In sum, we report the relationships between several local management factors, as well as landscape surroundings, and implications for garden management.